Athletic Shoulder Test Differences Exist Bilaterally in Healthy Pitchers - Aaron Trunt; Brandon T. Fisher; Lisa N. MacFadden (North American Sports Medicine Institute, 2022)
# Background There is a lack of valid and reliable tests that assess upper extremity strength and function for rehabilitation and injury prevention purposes in throwing athletes. The Athletic Shoulder (ASH) test has been proposed as a reliable measure of shoulder strength, but has not yet been studied in baseball pitchers. # Hypothesis/Purpose The purpose of this study was to establish values for healthy baseball pitchers performing the ASH test, compare those values with other common tests of shoulder strength and function, and compare ASH test performance bilaterally. It was hypothesized that the dominant arm would perform significantly better on the ASH test compared to the non-dominant arm. A secondary purpose of the study was to evaluate if ASH test performance was related to fastball velocity in baseball pitchers. It was hypothesized that ASH test performance would positively correlate with fastball velocity. # Study Design Cross-Sectional Study # Methods College and high school baseball pitchers were recruited to complete shoulder range of motion (ROM), isokinetic shoulder strength, and isometric shoulder strength testing using the ASH test. The ASH test was used to assess force production as a proxy for strength bilaterally at four levels of shoulder abduction (0°, 90°, 135°, and 180°), using a force plate. Approximately one-week later subjects returned for a bullpen session where fastball velocity was recorded with a radar gun. Bilateral differences in passive ROM, isokinetic, and isometric shoulder strength were examined using paired t-tests while linear relationships between isometric shoulder strength and fastball velocity were assessed using Pearson correlations. # Results Thirty-five healthy pitchers participated in the study (19.7 ± 1.8 years). Pitchers demonstrated significantly greater isometric shoulder strength at the 90° and 135° abduction positions with the throwing arm compared to the non-throwing arm. Pitchers also demonstrated commonly observed musculoskeletal adaptations in the throwing arm such as increased passive external rotation, decreased passive internal rotation, and greater internal and external rotator strength during isokinetic testing. Peak force production during the ASH test was not related to fastball velocity. # Conclusion The ASH test is capable of detecting bilateral shoulder strength adaptations commonly observed in other clinical tests in healthy pitchers. Pitchers demonstrated greater isometric peak force during the ASH test at levels of shoulder abduction similar to those observed in pitching. While these results may be intriguing for clinical use, peak force from the ASH test was not correlated to fastball velocity in pitchers, and therefore should be used with caution for predictions in this realm. # Level of Evidence 2 # Clinical Relevance A need exists for objective measures of shoulder strength for rehabilitation and injury risk monitoring in throwing athletes that are easy to administer, have high reliability and validity, and provide minimal re-injury risk to athletes recovering from injury. # What is known about the subject Data from the ASH test has been published previously in non-throwing athletes and was shown to be valid and reliable in that group. However, the test has not been explored widely in throwing athletes who are known to have significant musculoskeletal adaptations to the throwing shoulder. # What this study adds to existing knowledge The results from this study confirm that the ASH test is sensitive enough to detect the adaptations that are present in the healthy throwing athlete's shoulder. Due to the prior proven validity and reliability and these results, the test can be used to monitor throwing arm strength and function during rehabilitation or as a pre/intra-season screening tool to help describe arm health.